Do cell towers help increase vaccine uptake? Evidence from Côte d’Ivoire - Moussa Ouattara Zieh; Takeuchi Kenji (Open Health)
Cell towers enable the dissemination and access to vaccine information through mobile networks. In developing regions where mobile device sharing is common, the benefits of cell tower connectivity extend beyond individual mobile device ownership. This study provides valuable insights into how access to these communication infrastructures affects vaccination coverage and empirically examines the extent to which it enhances vaccine uptake. Combining geocoded cell tower information with data from a nationally representative household survey in Côte d’Ivoire, we found that proximity to cell towers was associated with higher vaccine uptake. Every unit decrease in the distance to cell towers was associated with about two additional children vaccinated per 1,000 population. Using the instrumental variable to address endogeneity in cell tower distribution, the finding aligns with that obtained using OLS.